Inte‐grating satellite remote sensing and spectro-radiometric measurements for monitor‐ing archaeological site landscapes - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Ioannides, Marinos; Clayton, Chris R I (My University, 2008)
This paper explores the beneficial integration of both satellite remote sensing and in-situ spectroradiometric measurements forimproving the available post-processing techniques in monitoring landscape changes in the vicinity of archaeological sites. Thestudy has been conducted in the Kato Paphos archaeological area in the Paphos District area in Cyprus. Spectral signatures of different target areas have been measured in-situ using the GER1500 and SVC HR-1024 field spectro-radiometers. Classification and change-detection techniques have been applied for the available archived Landsat TM images and high-resolution Quickbird and IKONOS images.
Keywords: Satellite remote sensing; Spectral signature; Spectro-radiometric measurements; Archaeology